INTERPRETASI KONTEKSTUAL (Studi Pemikiran Hermeneutika Al-Qur’an Abdullah Saeed) - Sovia, Sheyla Nichlatus (Dialogia: Jurnal Studi Islam dan Sosial, 2015)
Abstract: The existence of al-Qur'an as Muslim guidance is the last decision; its presence is most fundamental for Muslims. Al-Qur’an is not only as reading text but also as a reference in daily life. However, al-Qur’an as guidance, in fact, why does it frequently occur a significant difference between its own adherents? The answers are due to different interpretations among them, most Muslims have a tendency to believe in a literal interpretation, while others supposed to contextual interpretation method because it is considered more appropriate. Abdullah Saeed offered contextual interpretation to address this issue; he campaign the importance of contextual interpretation based on the spirit of the age. Exploring the importance of contextual interpretation Abdullah Saeed includes: First, the hermeneutic of al-Qur’an; Saeed focused on ethico-legal verses. Saeed considered this verse is often interpreted literally an sich and ignore the context of revelation and interpretation. Secondly, before establishing all interpretation models, Saeed organized theoretical foundation for contextual interpretation by reading and critiquing tradition of interpretation of al-Quran. Third, Saeed’s hermeneutic known as a continuation of Fazlurrahman’s hermeneutic. The theoretical foundations of Saeed’s contextualization interpretation are first, the link between revelation and socio-historical context surrounding them; second, the phenomenon of flexibility in how to read al-Quran. Third, internally al-Qur’an cannot be understood as such textual approach in hence it should know in what context its verses are read.Keywords: Penafsiran Tekstual, Sab’at Ah}ruf, ethico-legal texts dan Interpretasi Proto   Contextualist